GLOBAL COMPARISONS OF VOLCANIC-ASSOCIATED MASSIVE SULPHIDE DISTRICTS - Allen R.L.; Weihed P.; Blandell D.; Crawford T.; Davidson G.; Galley A.; Gibson H.; Hannington M.; Herrington R.; Herzig P.; Large R.; Lentz D.; et al. (My University, 2002)
Although volcanic-associated massive sulphide (VMS) deposits have been studied extensively, the geodynamic processes that control their genesis, location and timing remain poorly understood. Comparisons among major VMS districts, based on the same criteria, have been commenced in order to ascertain which are the key geological events that result in high-value deposits. The initial phase of this global project elicited information in a common format and brought together research teams to assess the critical factors and identify questions requiring further research. Some general conclusions have emerged. (1) All major VMS districts relate to major crustal extension resulting in graben subsidence, local or widespread deep marine conditions, and injection of mantle-derived mafic magma into the crust, commonly near convergent plate margins in a general back-arc setting. (2) Most of the world-class VMS districts have significant volumes of felsic volcanic rocks and are attributed to extension associated with evolved island arcs, island arcs with continental basement, continental margins, or thickened oceanic crust. (3) They occur in a part of the extensional province where peak extension was dramatic but short-lived (failed rifts). In almost all VMS districts, the time span for development of the major ore deposits is less than a few million years, regardless of the time span of the enclosing volcanic succession. (4) All of the major VMS districts show a coincidence of felsic and mafic volcanic rocks in the stratigraphic intervals that host the major ore deposits. However, it is not possible to generalize that specific magma compositions or affinities are preferentially related to major VMS deposits world-wide. (5) The main VMS ores are concentrated near the top of the major syn-rift felsic volcanic unit. They are commonly followed by a significant change in the pattern, composition and intensity of volcanism and sedimentation. (6) Most major VMS deposits are associated with proximal (near-vent) rhyolitic facies associations. In each district, deposits are often preferentially associated with a late stage in the evolution of a particular style of rhyolite volcano. (7) The chemistry of the footwall rocks appears to be the biggest control on the mineralogy of the ore deposits, although there may be some contribution from magmatic fluids. (8) Exhalites mark the ore horizon in some districts, but there is uncertainty about how to distinguish exhalites related to VMS from other exhalites and altered, bedded, fine grained tuffaceous rocks. (9) Most VMS districts have suffered fold-thrust belt type deformation, because they formed in short-lived extensional basins near plate margins, which become inverted and deformed during inevitable basin closure. (10) The specific timing and volcanic setting of many VMS deposits, suggest that either the felsic magmatic-hydrothermal cycle creates and focuses an important part of the ore solution, or that specific types of volcanism control when and where a metal-bearing geothermal solution can be focused and expelled to the sea floor, or both. This and other questions remain to be addressed in the next phase of the project. This will include in-depth accounts of VMS deposits and their regional setting and will focus on an integrated multi-disciplinary approach to determine how mineralisation, volcanic evolution and extensional tectonic evolution are interrelated in a number of world-class VMS districts.